Limits of the employee’s responsibility for his functional errors in the disciplinary and penal areas (Journal of Misan Researches, 2022)
The idea of this ​​research lies in the necessity of protecting the dignity of the employee and his/her administrative rights from being infringed without legal justification or legal procedures with emphasis on the necessity of commitment to implementing the provisions of the article of the Discipline Code about the administrative investigation with the employee before referring him/his for a crime has been never shown and preparing a defense on its basis which lead to the derogation of rights, and suspicions and hearsay against the employee. Consequently, the position of the employee may destabilize and his/her relationship with the job may be threatened, Hence, it requires that the administrative investigation should precede the criminal investigation in the administrative infringements. The administrative investigation could be of a productive impact in the criminal case and the courts of penalty in charging and convicting the employee in cases the competent court finds the witness statements, as well as other evidence which helps it in reaching the truth, not as some, think that the minutes of the investigative committees can not be promoted to the evidence on which the conviction of the court is built toward the accused,  so this research discusses in the first study the primacy of the administrative investigation and its impact on the criminal case through the legal basis of precedence in addition to discussing its.